Study on Dynamic Mechanical Properties and Failure Mechanism of Sandstones under Real-Time High Temperature. (8th December 2021) - Zhang, JiaZhi; Li, Ming; Lin, Gang; Zhang, Lianying; Yu, Hao; Di, Kui
Abstract : The research on dynamic mechanical properties of rocks under high temperature is the basis for safe and efficient implementation of deep coal mining and underground coal gasification engineering. In this paper, the split Hopkinson bar (SHPB) with real-time high-temperature function was adopted to systematically study dynamic mechanical properties of sandstones. The research showed that under the condition of a fixed temperature, with the increase of strain rate, the dynamic compressive strength and dynamic peak strain of sandstone increased gradually, and the variation of dynamic elastic modulus with strain rate was not obvious. With the increase of temperature, the dynamic compressive strength of sandstone increased first and then decreased, the dynamic peak strain increased gradually, and the dynamic elastic modulus decreased overall. The variation law of macroscopic failure mode and energy dissipation density with temperature was revealed, and the change mechanism was explained considering the influence of high temperature on the internal structure of sandstone. Based on the principle of component combination and the theory of micro-element strength distribution, the dynamic statistical damage constitutive model was established, and its parameters had certain physical significance. Compared with the experimental results, the established model can well describe the dynamic stress-strain relationship of sandstone under real-time high temperature.